Multiple Values and System Mechanisms of Rice Terrace Systems from the Perspective of Heritage Comparison - Yuliang YANG; Xuerun YU; Yuanmei JIAO; Songlin SUN (Fengjing Yuanlin)
ObjectiveTerraced fields are common around the world, and those with high quality, such as Honghe Hani Rice Terraces in China, Rice Terraces of the Philippine Cordillera in the Philippines, and Subak Irrigation System in Indonesia, have all been listed as cultural landscape heritage in the World Heritage List published by UNESCO. The kind of heritage with terraces as the main body also belongs to cultural landscape heritage, intangible cultural heritage, Globally Important Agricultural Heritage Systems and World Heritage Irrigation Structures, showing that this kind of heritage has extremely rich heritage value. However, it is likely to be confused about the mutual relationships between many heritage values owned by the same object and the generating reasons for such relationships. This research aims to, by explaining the concept of rice terrace system and clarifying the system mechanism and generation principle of its connotation, provide an important theoretical and practical reference for the mining and protection of multiple values of rice terrace systems.MethodsThis research analyzes relevant official texts classified into different heritage systems, discusses the value connotations of rice terrace system in different heritage systems and, based on the principle of generative wholeness, selects typical heritage cases of rice terrace system such as Honghe Hani Rice Terraces, Ziquejie Terraces, Longji Rice Terraces, Ifugao Rice Terraces and Bali Terraces for comparative research, with a focus on their respective outstanding values.ResultsIn terms of text connotation, the multiple values of rice terrace systems derived from the same spatial elements can simultaneously meet the universal standards of different heritage systems. Rice terrace systems also have the attributes of cultural landscape, agricultural production, irrigation engineering, concepts and customs, so that different evaluation criteria point to the same object. Among cultural landscapes, the Globally Important Agricultural Heritage Systems focus on the main body of the agricultural system, and the World Heritage Irrigation Structures focus on engineering characteristics. These two types of special heritage aim to interpret a certain outstanding value of cultural landscape heritage from a new perspective, so as to improve and deepen the understanding of the value of cultural landscape heritage, but such interpretation should not become a deconstruction of the overall value of cultural landscape heritage. Through analyzing the Honghe Hani Rice Terraces, Ziquejie Terraces, Longji Rice Terraces, Ifugao Rice Terraces and Bali Terraces, the research figures out that each rice terrace system consists of five subsystems: With nature as the foundation, terrace as the core, village as the purpose, irrigation as the support, and concept as the survival cornerstone, the five subsystems together constitute a complex system, with their dominant values constituting the overall value of a rice terrace system. Specifically, the “three levels” of nature, terrace and village form a highly self-consistent and inseparable complex system through the “two connections” between material systems and between non-material system and material system.ConclusionWith the concept of rice terrace system, this research expounds the multiple value characteristics and system mechanisms of the world heritage system with terrace as the main body. The main conclusions are as follows. 1) There are extensive crossover and complex associations between different heritage systems, and rice terrace system is a typical object with such crossover and correlation characteristics, which serve as an important source of multiple values of rice terrace system. 2) In terms of text connotation, the multiple values of rice terrace system derived from the same spatial elements can simultaneously meet the universal standards of different heritage systems. The value of cultural landscape heritage is rooted in the interaction between people and land with rice production mode as the core, which has the basic occurrence level and constitutes a comprehensive heritage. The Globally Important Agricultural Heritage Systems, World Heritage Irrigation Structures and intangible cultural heritage all emphasize the value of cultural landscape heritage in a certain aspect and belong to special heritage. 3) In terms of the system mechanism, the multiple values of a rice terrace system originate from the composition of and mutual relationship within the system. Each rice terrace system is composed of five subsystems, namely the nature, terrace, village, irrigation and concept subsystems; each subsystem follows the principle of generative wholeness, with the “three levels” of nature, terrace and village, through the “two connections” between material systems and between material system and non-material system, forming a highly self-consistent complex system, and showing the overall value featuring the integration of diversity and unity. In future heritage protection systems, the elaboration of extensive crossover and multiple values will certainly be an important trend. As the meeting point of multiple heritage systems, rice terrace systems can contribute systematic thinking to the exchange of different heritage types. Taking agriculture as the noumenon, rice terrace systems face unprecedented changes and challenges in contemporary times. The failure to put forward effective response strategies in the aspects of heritage activation and utilization, as well as value continuation and inheritance is the deficiency of the research, which needs to be addressed in future research.